Patterns of mortality by occupation in the UK, 1991â2011: a comparative analysis of linked census and mortality records - Srinivasa Vittal Katikireddi, Dr, PhD; Alastair H Leyland, Prof, PhD; Martin McKee, Prof, MD; Kevin Ralston, PhD; David Stuckler, Prof, PhD (Elsevier, 2017)
Summary: Background: Detailed assessments of mortality by occupation are scarce. We aimed to assess mortality by occupation in the UK, differences in rates between England and Wales and Scotland, and changes over time in Scotland. Methods: We analysed adults of working age (20â59 years) using linked census and death records. Main occupation was coded into more than 60 groups in the 2001 census, with mortality follow-up until Dec 31, 2011. Comparable occupation data were available for Scotland in 1991, allowing assessment of trends over time. We calculated age-standardised all-cause mortality rates (per 100â000 person-years), stratified by sex. We used Monte Carlo simulation to derive p values and 95% CIs for the difference in mortality over time and between England and Wales and Scotland. Findings: During 4Â·51 million person-years of follow-up, mortality rates by occupation differed by more than three times between the lowest and highest observed rates in both men and women. Among men in England and Wales, health professionals had the lowest mortality (225 deaths per 100â000 person-years [95% CI 145â304]), with low rates also shown in managers and teachers. The highest mortality rates were in elementary construction (701 deaths per 100â000 person-years [95% CI 593â809]), and housekeeping and factory workers. Among women, teachers and business professionals had low mortality, and factory workers and garment trade workers had high rates. Mortality rates have generally fallen, but have stagnated or even increased among women in some occupations, such as cleaners (337 deaths per 100â000 person years [95% CI 292â382] in 1991, rising to 426 deaths per 100â000 person years in 2001 [371â481]). Findings from simulation models suggested that if mortality rates by occupation in England and Wales applied to Scotland, 631 fewer men (95% CI 285â979; a 9Â·7% decrease) and 273 fewer women (26â513; 6Â·7% decrease) of working age would die in Scotland every year. Excess deaths in Scotland were concentrated among lower skilled occupations (eg, female cleaners). Interpretation: Mortality rates differ greatly by occupation. The excess mortality in Scotland is concentrated among low-skilled workers and, although mortality has improved in men and women in most occupational groups, some groups have experienced increased rates. Future research investigating the specific causes of death at the detailed occupational level will be valuable, particularly with a view to understanding the health implications of precarious employment and the need to improve working conditions in very specific occupational groups. Funding: None.